The Monarchy and the Transition to Democracy in Spain - S. M. Khenkin (Контуры глобальных трансформаций: политика, экономика, право, 2018)
In the 1970s, the Spanish monarchy, represented by King Juan Carlos I, appeared in an unexpected role of the initiator of radical social change. Juan Carlos, the grandson of King Alfonso XIII, deposed in 1931, was brought up by Franco. After the death of Caudillo in November 1975, he assumed the post of head of state. Initially, the king, who shared liberal views, was in a very difficult situation. He was considered as a heir of Franco, he was deprived of democratic and dynastic legitimacy. Juan Carlos managed to appoint his trustees – T. Fernandez-Miranda and A. Souares to key government posts. They had carried out a number of reforms and as a result dismantled the authoritarian Franco regime and led the country to democracy. The king himself, remaining behind the scenes, acted as an arbiter, a “motor” and patron of the process of changes. In Spanish society, the indifference and even the negative attitude towards the monarchy was replaced by confidence in the necessity and usefulness of this institution. Unfortunately, in the last years of the reign of Juan Carlos, his popularity fell sharply due to corruption scandals in the royal family. However, giving an overall assessment of the role of Juan Carlos in Spanish history, the first place should be given to his services, not mistakes. The Spaniards at one time adopted a monarchy, because they were subdued by the king, and not by the monarchy as an institution.